BRDF Importance Sampling for Linear Lights - Peters, Christoph (Computer graphics forum, 2021)
We introduce an efficient method to sample linear lights, i.e. infinitesimally thin cylinders, proportional to projected solid angle. Our method uses inverse function sampling with a specialized iterative procedure that converges to high accuracy in only two iterations. It also allows us to sample proportional to a linearly transformed cosine. By combining both sampling techniques through suitable multiple importance sampling heuristics and by using good stratification, we achieve unbiased diffuse and specular real‐time shading with low variance outside penumbrae at two samples per pixel. Additionally, we provide a fast method for solid angle sampling.